Improvement of Fuzzy Based Practical Controller for Continuous Motion Control - Purtojo Purtojo; Heru S. B. Rochardjo; Gesang Nugroho; Herianto Herianto (Institute of Advanced Engineering and Science, 2015)
This article presents a development of a fuzzy based nominal characteristic trajectory following (NCTF) controller for continuous motion control. A new structure is proposed in order to achieve excellent performance of tracking to a continuous reference input and also for point-to-point positioning task. The proposed structure maintains the NCTF controller simple configuration which is composed of a nominal characteristic trajectory (NCT) and a compensator. The compensator is based on a Mamdani type fuzzy controller. Its membership functions are designed according to the available information provided by NCT and the hardware specification. Controller performance was evaluated through simulation by comparing it with the existing method previously proposed for the fuzzy based NCTF controller. The tracking performance was evaluated by measuring responses of the system providing continuous sinusoidal signal input. The result indicates that substantial improvement is achieved in tracking of continuous reference inputs. Moreover, a better result is also obtained in performing point-to-point positioning task.DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.7008